MOTIVASI ORANG TUA DALAM MENINGKATKAN HAFALAN AL-QURAN SANTRI PONDOK PESANTREN RIYADLUL QUR’AN MOJOKERTO - Abdul Rouf; Imam Mashudi Latif; Rodotun Nikmah (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2023)
The aim of this research is to determine the motivation of parents in improving the memorization of the Al-Qur'an by students at the Riyadlul Qur'an Islamic Boarding School in Mojokerto. This type of research is descriptive qualitative, data collection techniques use direct observation, interviews and documentation. The data analysis technique uses the Miles and Huberman model data analysis technique, namely through data reduction, data presentation, and conclusions or verification. The results of the research show that parents' motivation in increasing the memorization of the Al-Qur'an by students at the Riyadlul Qur'an Islamic Boarding School in Mojokerto is in the good category. This is proven by: The students are more disciplined and focused in memorizing the Al-Quran, the relationship between the students' teachers and parents is well established, the memorization targets are fulfilled according to boarding school standards, and the students' memorization is getting faster and better. Several supporting factors in student motivation are: The student's intelligence factor, the student's age, and sufficient and flexible time to memorize. While the inhibiting factors are; The emergence of laziness in students, students' difficulty in memorizing and students' boredom in memorizing.